PENERAPAN ETIKA ADMINISTRASI PUBLIK DALAM MENINGKATKAN KUALITAS PELAYANAN DI KANTOR KECAMATAN LAROMPONG SELATAN KABUPATEN LUWU - Sulfiyah, Alfiyana; Burhanuddin, Burhanuddin; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2023)
ABSTRACT The purpose of the study was to determine the Application of Public Administration Ethics in Improving Service Quality at the Larompong Selatan District Office, Luwu Regency. The method used in this study is a qualitative method. Data collection techniques using observation, interviews, and documentation. The results of this study indicate that the Application of Public Administration Ethics in Improving Service Quality at the Larompong Selatan District Office, Luwu Regency shows that in terms of equality it has been carried out optimally without any discrimination. Justice, in this case, employees serve the community in a friendly manner, all people are treated equally. Loyalty in this case, especially for female employees who are IRT cannot be said to be optimal because there are still some who are late in entering the office. The responsibilities given in public services have been going well, regarding employees at the Larompong Selatan District Office, Luwu Regency who carry out their duties in accordance with their respective tupoksi. Kata kunci: Penerapan Etika, Administrasi Publik, Kualitas Pelayanan